Light-Emitting Diode An Outlook On the Empirical Features and Its Recent Technological Advancements - Thirumalai, Jagannathan (IntechOpen, 2018)
The broad vision of this book is to offer book lovers a comprehensive appraisal of topics in the global advancements of experimental facts, instrumentation, and practical applications of LED and OLED materials and their applications. The prime feature of this book is connected with LED and OLED materials approaches of fabrication, optimization limits, and their extensive technical applications. This book is comprised of seven chapters encompassing the importance of LEDs and OLEDs, the history of LEDs and OLEDs with necessary examples, the phototoxic-cum-bactericidal effect due to the usage of blue LED irradiation, DC network indoor and outdoor LED lighting, WLEDs with thermally activated delayed fluorescence emitters, tetradentate cyclometalated platinum (II) complex-based efficient organic LEDs, the impact of the use of large LED lighting loads in low-voltage networks, highly efficient OLEDs using thermally activated delayed fluorescent materials, and AlGaN deep ultraviolet LEDs. Individual chapters provide a base for the wide range of common bibliophiles in diversified fields, students, and researchers, who may conduct research pertinent to this book and will find simply explained basics as well as advanced principles of designated subjects related to these phenomena. The book was created from seven contributions from experts in the diversified fields of LED and OLED fabrication and technology from over 15 research institutes across the globe.